Development of new spectroscopic instrument for enivronmental measurements of gases from industries and volcanoes - Matisans, Modris (My University, 2010)
Refineries and petrochemical industries are large point sources of volatile organic compounds. These gases are active in tropospheric chemistry and produce photochemical smog. In order to complement the arsenal of instruments for fugitive gas measurements a new instrument has been developed following a theoretical investigation of a previous master thesis. The new instrument is a so called non dispersive spectrometer which will replace the infrared spectrometer in a solar occultation flux (SOF) instrument, currently used at the Radio and Space department. This new device is aimed to be inexpensive, light weight and robust. In the SOF method gas flux measurements are conducted using the sun as the light source and by observing the amount of light transmitted through the plume of gas. Further, wind speed data are used to determine gas emission flux in mass per time units. In this work the non-dispersive spectrometer was designed, built and tested in the laboratory as well as in the field. In the instrument the sun, from a so called solar tracker, is transmitted through an entrance opening with 2.54 cm in diameter. The light is further transmitted through a filter wheel, with a set of bandpass filters, to a PbSe infrared light sensor that records the varying voltage reading for each filter consequently as the wheel rotates at a speed of 6 to 7 Hz. Thereafter, filter transmittance measurements are used to calculate the alkane column density. The filters are also used to compensate for the presence of water and methane as well as a slope in detector sensitivity over operating region. In a field test, the non-dispersive spectrometer was combined with a solar tracker and positioned on a pickup car. Measurements were then conducted downwind a refinery revealing alkane mixture carbon number of 4.6 and emission estimation of 122 kg/h. This was consistent with SOF measurements that were being conducted in parallel.
Keywords: Fysik; Physical Sciences